Тенденції та стратегія розвитку туризму в Україні ХХІ ст - Бондарчук–Чугiна І. Ю. (Hileya: Scientific Bulletin / Gileya, 2018)
The tendency of the development of «cultural tourism» in Ukraine is determined in the article. The analysis of the regional approach as for the defining of the Ukrainian cultural-and-historical potential is given; the strategies of tourist activity management in Ukraine are suggested.